KERANGKA SISTEM PENGUKURAN INTERNET SEBAGAI REKOMENDASI PENYEDIA DAN PENGGUNA INTERNET - Winarno Sugeng; Jazi Eko Istiyanto; Khabib Mustofa (Universitas Sriwijaya, 2012)
AbstractInternet measurement is now essential, many different people and organizations have an interest in measuring the internet. But broadly speaking, the interest in internet measurement arises for three kinds of reason: commercially, socially, and technically. The Internet is very complex, so it is very difficult to understand. Therefore, there is a need for a framework to be proposed for the Internet measurement system which dedicated to Internet service providers and users. It is hoped the finally is not only the effectiveness factors are achieved, but the satisfaction of users of Internet services can be achieved. The discussion in this paper will be preceded by an understanding of: Internet Architecture, Internet Measurements, Network Management, Network Monitoring Tools, Real-Time System, Review of QoS, QoS monitoring, and finally the proposed internet measurement system architecture with QoS guarantees real-time system-based.Keywords: internet measurement, QoS guarantee, real-time system